Pemberdayaan Masyarakat melalui Pelatihan Konsep Ideal Gizi Anak di Desa Waru Kabupaten Bogor - Jati, Diyen Marror (Jurnal Pemerintahan dan Politik, 2025)
This article discusses the process of community empowerment through training on the ideal concept of nutrition for children at Posyandu Badra 1, Waru Village, Bogor Regency. The ideal concept in community empowerment is a long-term program by monitoring the activity calendar, such as the community as the beneficiary, so that the output of the community can grow and develop by living independently after consistently attending nutrition classes. This research method uses qualitative research because food independence is an individual taste for each child. This research wants to see how the community is consistent in providing the best nutrition for children during the golden age period for 0-2 years by looking at the community's consistency in attending nutrition classes with 10 people for 21 days. The purpose of this article is to evaluate the effectiveness of the CSR Health program in Community Empowerment in Waru Village. The results of this research article are that only 2-3 people in the community who took the nutrition class consistently attended the nutrition class until the end by look at the documentation of ideal concepts in child nutrition through a shared calendar. This research was quite effective for the first time a Community Empowerment Health CSR Program was held in Waru Village, Bogor Regency.